As-cast and extruded MgZnCa systems for biodegradable implants: Characterization and corrosion behavior - Lara Moreno; Endzhe Matykina; Kiryl A. Yasakau; Carsten Blawert; Raul Arrabal; Marta Mohedano (Journal of Magnesium and Alloys, 2023)
The aim of the present study is to evaluate the effect of alloy processing and composition as well as the pH control and testing medium on the in vitro corrosion performance of MgZnCa systems for biodegradable implants. The grain size and secondary phases were analyzed by optical microscopy, scanning electron microscopy, transmission electron microscopy, and X-ray diffraction. Scanning kelvin probe force microscopy (SKPFM) was used to analyze the Volta potential values of the second phases. The corrosion performance of the three alloys was evaluated by electrochemical and hydrogen evolution methods in α-MEM with and without organic species (i.e. complete and inorganic α-MEM). Two strategies were followed to evaluate the influence of the pH on the corrosion behavior: daily solution replacement and CO2 flow based pH control. For all the materials, the organic medium accelerates the corrosion process. Constant pH maintained by CO2 flow through the medium results in considerably higher corrosion rates for all alloys. The impact of pH is lesser on the as-cast alloys due to the barrier effect of the secondary phases, particularly pronounced in the Mg1Zn1Ca alloy which showed the lowest corrosion rate. The wrought Mg0.5Zn0.2Ca alloy that lacks the refined secondary phase network and exhibits high number of twins undergoes accelerated uniform corrosion under constant pH conditions.